Cover Feature: Synthetic, Structural, and RNA Binding Studies on 2‐Aminopyridine‐Modified Triplex‐Forming Peptide Nucleic Acids (Chem. Eur. J. 17/2019). Issue 17 (4th March 2019) - Kotikam, Venubabu; Kennedy, Scott D.; MacKay, James A.; Rozners, Eriks
Abstract : Biophysical and NMR‐structural studies uncover an unexpected interplay of electronic and structural properties of nucleobase modifications in triple helices formed by peptide nucleic acid (PNA) and double‐stranded RNA. Contrary to expectations, modification of 2‐aminopyridine nucleobase with the electron‐donating 4‐methoxy group did not stabilize the triplex. The cover picture shows the first NMR structure of a PNA–RNA triplex. Steric and electronic repulsion between the oxygen of a 4‐methyxy group and the oxygen of the carbonyl connecting the adjacent PNA nucleobase to the PNA backbone is identified (note red spheres) as the likely cause of triplex destabilization. More information can be found in the Full Paper by E. Rozners et al. onpage 4367 .